Improving thermoelectric properties of Cu2O powder via interface modification. (1st December 2022) - Zhang, Mengyuan; He, Xuting; Xue, Yuli; Lin, Zedong; Tong, Ning-Hua; Lai, Wenzhen; Liang, S.
Abstract: We report thermoelectric properties of Cu2 O powder through interface modification. Seebeck coefficient (SC) of Cu2 O–Au composite powder was measured to be 900–1500 μV/K in the temperature range of 300–420 K, and power factor was ∼1.95 μW/m⋅K 2 at 420 K, in contrast to raw Cu2 O powder (0.86 μW/m⋅K 2 ). The improved Seebeck coefficient and power factor relate very likely to the band structure modification by Au atoms, energy filtering and remote doping. Optic measurement and band structure calculated using density functional theory confirmed the band gap of Cu2 O–Au composite powder (1.78eV) is slightly narrower than the raw Cu2 O powder (1.85eV) and higher electronic density of states (DOS) in the conductance band of Cu2 O–Au composite powder. Powder form thermoelectric devices (P-TE) easily prepared by pressing in a die without sintering might offer an alternative paradigm for mass fabrication with low cost. The high Seebeck coefficient and power factor of P-TE could find applications as power generator, temperature/touch sensors, transient thermoelectric coolers, etc. Highlights: We measured Seebeck coefficient of Cu2 O powder as high as 1500 μV/K. A very facile fabrication process was used (No ball milling, no sintering):Cu2 O powder deposited of Au by sputtering. Band structure modification by Au atoms, energy filtering and remote doping for improved thermoelectric performance.